EUCARISTIA E PASTORAL - Hortal, Jesus (Perspectiva Teológica, 1976)
In the first part of this article Jesus Hortal presents the pastoral dimensions of the Eucharist. Pastoral is understood as the freeing christian praxis which leads to salvation. The author discovers three functions in Pastoral: a prophetic function - announcing the Word; a sacerdotal function - worship; a king function - service of unity.